Designing Employee Attendance Application Using Location-Based Service (LBS) Based on Android - Hutasoit, Rutmian Mariama; Fahmi Ruziq; Mayang Mughnyanti (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
The rapid growth of information and communication technology in Indonesia has heightened the need for fast, reliable data access, especially for organizations managing large, distributed workforces. This study proposes an Android-based attendance application using Location-Based Service (LBS) to address the limitations of the current web-based HR system at PT Infomedia Solusi Humanika (ISH), a Human Capital Services provider under the Telkom Group. ISH oversees over 28,000 employees across 420 cities, yet the existing system struggles to support attendance tracking for employees at client offices, affecting records such as leave, performance, and payroll. To solve this, an Android application utilizing the Haversine Formula for accurate location mapping within a 100-meter radius allows employees to log attendance remotely. Developed using the Rapid Application Development (RAD) method, the app enables employees to handle attendance, leave requests, and overtime tracking directly through their mobile device, removing the need to access a browser. This solution enhances usability, increases HR efficiency, and ensures accurate performance records, supporting ISH's reputation as a modern HR management provider.